2019
DOI: 10.1029/2019gb006305
|View full text |Cite
|
Sign up to set email alerts
|

Do Oceanic Hypoxic Regions Act as Barriers for Sinking Particles? A Case Study in the Eastern Tropical North Atlantic

Abstract: In oxygen minimum zones (OMZs), the attenuation rates of particulate organic carbon (POC) fluxes of large particles are known to be reduced, thus increasing the efficiency with which the biological carbon pump (BCP) transfers carbon to the abyss. The BCP efficiency is expected to further increase if OMZs expand. However, little is known about how the POC fluxes of small particles—a significant component of the BCP—are attenuated inside OMZs. In this study, data collected by two BGC‐Argo floats deployed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Another possible mechanism for the high correlations in the fourth regime may be related to particle remineralization process. A recent study by Rasse and Dall'Olmo (2019) found a permanent layer of small particles linked to microbial communities located in the upper section of the oxygen minimum layer, and they further showed that attenuation of small‐particle fluxes was equivalent or significantly higher inside the oxygen minimum layer. The layer of small particles above the oxygen minimum layer could be caused by the zooplankton fragmentation of large particles into small particles (Briggs et al, 2020; Cavan et al, 2017), as many zooplankton migrate during the day into the low oxygen core or the upper boundary of the oxygen minimum layer (Steinberg et al, 2008; Wishner et al, 2018, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Another possible mechanism for the high correlations in the fourth regime may be related to particle remineralization process. A recent study by Rasse and Dall'Olmo (2019) found a permanent layer of small particles linked to microbial communities located in the upper section of the oxygen minimum layer, and they further showed that attenuation of small‐particle fluxes was equivalent or significantly higher inside the oxygen minimum layer. The layer of small particles above the oxygen minimum layer could be caused by the zooplankton fragmentation of large particles into small particles (Briggs et al, 2020; Cavan et al, 2017), as many zooplankton migrate during the day into the low oxygen core or the upper boundary of the oxygen minimum layer (Steinberg et al, 2008; Wishner et al, 2018, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Our study supports the proposition that robotic observations of b bp and O 2 can be used to better delineate the N 2yielding section at the appropriate spatial (e.g., vertical and regional) and temporal (e.g., event, seasonal, interannual) resolutions. In addition, POM fluxes and N 2 can be simultaneously quantified using the same float technology (BGC-Argo, Bishop and Wood, 2009;Dall'Olmo and Mork, 2014;Reed et al, 2018;Boyd et al, 2019;Estapa et al, 2019;Rasse and Dall'Olmo, 2019). These robotic measurements can contribute to refining global estimates of N 2 production by better constraining both the oxygen-poor section where N 2 is produced and POM fluxes that fuel its loss.…”
Section: New Perspectives For Studying N 2 Yielding In Oxygen-deficiementioning
confidence: 99%
“…Studies from the OMZ in the eastern tropical Atlantic have shown that organic carbon flux attenuation of large particles is reduced, thereby increasing the efficiency of the biological carbon pump (Rasse and Dall'Olmo, 2019). However, small particles seem to react differently and show a normal to higher attenuation inside the OMZ compared to the outside where enough oxygen is available (Rasse and Dall'Olmo, 2019).…”
Section: Carbon Flux Attenuation and Transport Within Eddies And Under Oligotrophic Conditionsmentioning
confidence: 99%
“…However, if oxygen content is strongly reduced to hypoxic and suboxic conditions in the sub-surface and deeper waters, degradation of organic carbon may be reduced due to lower zooplankton grazing (e.g., Hauss et al, 2016). For the OMZ in the eastern tropical Atlantic, it is assumed that organic carbon attenuation of larger particles in the water column is reduced, thereby increasing the efficiency of the biological carbon pump (Rasse and Dall'Olmo, 2019). In the OMZs of the Pacific Ocean and the Arabian Sea, low carbon flux attenuation has been suggested in suboxic waters at depths between 100 and 1000 m (Weber and Bianchi, 2020).…”
Section: Introductionmentioning
confidence: 99%